THE EFFECT OF STRESSFUL EXERCISE AND / OR LOCAL IMPLANTS OF LABELLED BUFFY - Hani, Nawfal Fara’id; Haddad, Fara’id Y.S.; AL-Aazzawi, Hani T. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: